Dictionary of economic and statistical terms - Howell, James M.; Tolli, Donna J.; Nelson, Dawn D. (Washington, D.C. : U.S. Dept. of Commerce; [for sale by the Supt. of Docs., U.S. Govt. Print. Off.], 1969)
This dictionary was prepared as an aid to understanding and using the publications and press releases of the Bureau of the Census and the Office of Business Economics in the Department of Commerce. The dictionary is divided into four sections: the national income and product accounts; the balance of payments accounts; economic and statistical indicators; and economic and statistical terms.
"A United States Department of Commerce publication."
Includes index.
ne 14/09/2021
Ref.
Keywords: Economics; Statistics; United States